APPLICATION OF CORRELATION PORTRAIT IN THE DIFFERENTIAL DIAGNOSIS OF CARDIOVASCULAR, PULMONARY AND NERVOUS DISEASES - Vakulenko, D. V.; Vakulenko, L. O.; Kravets, N. O.; Kutakova, O. V.; Sverstiuk, A. S.; Lesiv, V. V. (Medical Informatics and Engineering, 2017)
An algorithm for constructing a correlation portrait of adaptation mechanisms of disease course during medical research is described in the article. The correlation portrait of the arterial oscillograms and electrocardiograms measurements for cardiovascular, pulmonary diseases, cerebral circulation disorders, and degenerative disc disease of the cervical spine and in healthy subjects is presented.